Pengaruh Media Pembibitan pada Pertumbuhan Setek Lada (Piper nigrum L.) - A. Bram Martin; Made Same; Wiwik Indrawati (Politeknik Negeri Lampung, 2015)
Growing medium influence plant growth and development. The purpose of this study was to determine the best growing medium used in the nursery of pepper (Piper nigrum L.). The experiment was conducted by using a randomized block design (RBD) with treatment: P0: subsoil, P1: subsoiland manure (2: 1), P2: subsoil and sand (2: 1), P3: subsoil, manure and sand (2: 1: 1), P4: topsoil, P5: topsoil and manure (2: 1), P6: top soil and sand (2: 1), P7: topsoil, manure and sand (2: 1:1). There are 8 treatment, 4 replicates of each treatment was repeated. Each experimental unit comprises 3 cuttings, cuttings planted each polybag, so there are 32 experimental units Â with overall there are 96 polybags. Based on the results of the study there were significant differences among the medium on the growth observed variables: shoot height, number of leaves, shoot diameter, shoot dry weight and root dry weight. Subsoil + manure (2: 1), subsoil + manure + sand (2: 1: 1), topsoil, topsoil + manure (2: 1), topsoil + manure + sand (2: 1: 1) provide good growth on cuttings of pepper, so it can be used in the nursery cuttings pepper.Keywords :pepper cutting, planting medium, seedling growthPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/22